2022
DOI: 10.1021/jacs.1c08152
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Analysis of the Water Oxidation Mechanism on Doped Nickel Oxides

Abstract: Metal oxides and oxyhydroxides exhibit state-of-the-art activity for the oxygen evolution reaction (OER); however, their reaction mechanism, particularly the relationship between charging of the oxide and OER kinetics, remains elusive. Here, we investigate a series of Mn-, Co-, Fe-, and Zn-doped nickel oxides using operando UV–vis spectroscopy coupled with time-resolved stepped potential spectroelectrochemistry. The Ni2+/Ni3+ redox peak potential is found to shift anodically from Mn- < Co- < Fe- < Zn-doped sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
97
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 79 publications
12
97
1
Order By: Relevance
“…52 However, kinetic analysis in Fe 2 O 3 containing different vacancy concentrations have shown that the OER rate determining step (RDS) is chemical in nature and is independent of the vacancy concentration. 53 Such discrepancy might be related to the chemical nature of the RDS 54,55 or to the difficulty in experimentally separating the contributions of vacancies within a large surface. As discussed below, further studies integrating modelling and experiments, are needed to unambiguously expose the role of defects and disorder in the catalytic mechanisms.…”
Section: Defect Formation and Surface Reactivitymentioning
confidence: 99%
“…52 However, kinetic analysis in Fe 2 O 3 containing different vacancy concentrations have shown that the OER rate determining step (RDS) is chemical in nature and is independent of the vacancy concentration. 53 Such discrepancy might be related to the chemical nature of the RDS 54,55 or to the difficulty in experimentally separating the contributions of vacancies within a large surface. As discussed below, further studies integrating modelling and experiments, are needed to unambiguously expose the role of defects and disorder in the catalytic mechanisms.…”
Section: Defect Formation and Surface Reactivitymentioning
confidence: 99%
“…8 Transition metals Ni-based catalysts have been extensively identified as a promising candidate for efficient OER owing to their intrinsic electron structure and high carrier mobility. [9][10][11][12] Various strategies have been well investigated for improving OER performance, including doping foreign metals, 13,14 creating heterojunction and defects, [15][16][17] morphology engineering, 18,19 and so on. Among these, introducing new transitional metal elements in Ni-based catalyst receives many attentions due to the capability of optimizing electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…7 The adsorption strength can be neither too strong nor too weak to attain the best activity, which can be described by the volcano-type activity plots. 8 According to the ''volcano'' model, the cost-effective cobalt-based materials have been considered as a group of promising candidates for the OER. 9 However, the catalytic efficiencies of cobalt-based electrocatalysts are still greatly limited by the kinetically sluggish surface adsorption and the formation of high valent Co active species.…”
mentioning
confidence: 99%
“…Reported studies have demonstrated that the introduction of a heteroatom is an effective way to produce a favourable electronic configuration and tune the adsorption energy. 8,10 For instance, Durrant and co-workers reported that a series of Mn-, Co-, Fe-, and Zn-doped nickel oxides can decrease the oxygen binding energetics and modulate the chemical rate-determining step during the OER. 8 Their studies found that the Fe-doped sample exhibits optimal binding energetics to achieve the highest OER activity, which confirmed the Sabatier principle experimentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation